2012
DOI: 10.5507/bp.2012.025
|View full text |Cite
|
Sign up to set email alerts
|

Prostate cancer - the role of magnetic resonance imaging

Abstract: Background. This article reviews the potential of magnetic resonance imaging (MRI) in prostate cancer diagnosis. Methods. Systematic scan of Pubmed, Ovid, Medline, Elsevier search engines was used, additional information was found through bibliographic review of relevant articles. Results. Substantial progress has been made in the imaging of prostate cancer in MR imaging, as well as in advanced MR spectroscopy. Conclusions. MRI is a non-invasive and direct imaging modality useful for cancer staging, therapy re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 26 publications
0
8
0
Order By: Relevance
“…Previous studies have demonstrated that DWI was a feasible method to detect PCa. Meanwhile, DWI was also considered to play an important role in monitoring therapy response, evaluating cancer aggressiveness and metastasis, guiding targeted biopsy and patient follow-up [49]. Nevertheless, all applications referred to above were based on an accurate diagnosis of PCa.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have demonstrated that DWI was a feasible method to detect PCa. Meanwhile, DWI was also considered to play an important role in monitoring therapy response, evaluating cancer aggressiveness and metastasis, guiding targeted biopsy and patient follow-up [49]. Nevertheless, all applications referred to above were based on an accurate diagnosis of PCa.…”
Section: Discussionmentioning
confidence: 99%
“…Several diagnostic procedures with different accuracy rate have been used for local tumor staging of PC. [9][10][11] One such modality is CT. The main role of CT in the evaluation of PC is nodal staging and detection of local advancement of tumor to adjacent structures; however, it has no significant efficacy in the assessment of primary tumors.…”
Section: Discussionmentioning
confidence: 99%
“…The main role of CT in the evaluation of PC is nodal staging and detection of local advancement of tumor to adjacent structures; however, it has no significant efficacy in the assessment of primary tumors. [11] MRI has been utilized to diagnose and stage PC. [11][12][13] reported a 13%-95% sensitivity and a 49%-97% specificity for MRI in the detection of extracapsular extension (ECE).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations